Business management - Rue, Leslie W. (Glencoe, 1994)
Business Management: Real-World Applications and Connections gives students an understanding of the way business works. It develops their technical knowledge and competence. Classroom experience is enhanced through a blend of text, visual presentation, and interactive resources